Biographical passages : essays in Victorian and Modernist biography : honoring Mary M. Lago - Lago, Mary; Law, Joe; Hughes, Linda K. (University of Missouri Press, 2000)
"Challenging the view that modern biographies are radically different from the straitlaced and ponderous Victorian tomes, Joe Law and Linda K. Hughes illustrate that continuities in biographical practice do exist, proving, for example, that the "tell-all" biography is not the exclusive preserve of the twentieth century. Enlisting the talents of biographers and scholars, Biographical Passages is an exploration of the art and craft of biography." "Law and Hughes conclude Biographical Passages with an epilogue in tribute to a scholar whose work is closely connected to all the essays in this collection - Mary Lago."--BOOK JACKET.